Kemampuan Mengalihwacanakan Teks Negosiasi ke Bentuk Narasi Mungganakan Model Problem Based Learning Siswa Fase E SMK Negeri 6 Padang - Zuraida Khairani; Najmi Hayati; Melati (JURNAL ARMADA PENDIDIKAN, 2025)
This study is motivated by the finding that students have not yet fully developed the skills to transform negotiation texts into narrative form, particularly in expressing ideas and understanding the transformation process. The study aims to describe the ability of Phase E students at SMK Negeri 6 Padang to transform negotiation texts into narratives using the Problem Based Learning (PBL) model. The research employed a descriptive quantitative method. The population consisted of 107 Phase E students in the 2024/2025 academic year, with a purposive sample of 35 students from Class X Culinary 3. Data were collected through a writing test in which students were asked to transform the negotiation text “Sewa Tanah” (sourced from the textbook) into a narrative text after learning through PBL. Students’ written work was assessed using an indicator-based scoring rubric and analyzed using descriptive statistics (means for each indicator and the overall mean). The results showed the mean scores for each indicator as follows: situation orientation 81.90 (Good), event development 74.28 (More than Adequate), rising conflict 67.62 (More than Adequate), climax 79.05 (Good), resolution 73.33 (More than Adequate), and coda 30.48 (Very Poor). The overall mean score was 69.20, which is below the minimum mastery criterion (KKTP) of 80.00. These findings indicate that PBL has not yet met the learning achievement standards for transforming negotiation texts into narratives in this context. The study recommends strengthening instruction focused on the stages of text transformation, providing intensive practice on weak indicators (especially the coda and conflict development), and improving lesson materials and the scoring rubric to help students’ achievement reach the KKTP.